Pending Agenda in Bankruptcy Issues in Peru - Corzo de la Colina, Rafael (2015)
This article addresses the issue referred to the modernization of the regulation on Bankruptcy matters in Peru. The authors propose the adoption of the Model of the United Nations Commission on International Trade Law by Peru to help update our national legislation on cross-border insolvency and create more efficient ways of recognizing insolvency proceedings that have been started abroad. Finally, the authors propose the updating of the nomenclature, which are used in certain provisions of the Civil Code, as part of the pending agenda on Bankruptcy Law in Peru.